Sensor Integrated CFRP Structures for Intelligent Fixtures. (2016) - Möhring, Hans-Christian; Wiederkehr, Petra; Lerez, Christoph; Schmitz, Holger; Goldau, Harald; Czichy, Charis
Abstract: In milling of impellers and blisks, critical workpiece vibrations of thin-walled blade structures occur due to the excitation by the process forces and the dynamic compliance of the sensitive elements of the parts. Workpiece vibrations lead to an inacceptable waviness and chatter marks on the blade surfaces and thus to the production of defective parts. Also, these vibrations provoke an increased tool wear progress. Within the European collaborative research project INTEFIX, fixture solutions are developed which enable the detection and compensation of chatter vibrations during machining of thin-walled workpiece elements. With respect to the machining of impeller blades, a challenging task is to identify critical vibrations by means of sensors which are integrated into the structure of the fixture or the contact surface between the workpiece and clamping system. This contribution introduces the integration and application of piezo patch transducers which are embedded in CFRP fixture components. The sensory CFRP sub-structure is located directly at the workpiece and pre-stressed by the clamping. Tests show the functionality and performance of the sensor system. In addition, the sensor integrated fixture is investigated in machining analyses.